Effects of CORM-3 formulations in in vitro and in vivo models of inflammation - Martins, Inês Mendonça Lourenço (2020)
CO-Releasing Molecules (CORMs) are a novel class of pharmaceutical agents able to release carbon monoxide (CO) to cells and tissues in a controlled manner, thus mimic the previously seen homeostatic properties of gaseous CO, namely in inflammatory processes, with neglectable toxicity. CO-Releasing Molecule 3 (CORM-3) is a ruthenium (Ru) carbonyl metal complex known to release one of its CO ligands when in contact with proteins, which have been used to describe metal-CORMs different roles and properties both in vitro as in vivo. Albumin is a key protein transporter of drugs in the bloodstream, therefore responsible for their pharmacokinetic profiles and ultimately efficiency. In the present work, UV-Vis analysis and fluorescent methods are used to study Bovine Serum Albumin (BSA) and CORM-3 interaction, showing little conformational changes upon CORM-3 incubation and an effective quenching described by the Stern-Volmer relationship. CORM-3 decomposition in the working phosphate buffer is also followed by UV-Vis spectroscopy showing a degradation rate constant of 0.0026 s-1 and a half-life of less than 5 minutes. This instability in water complicates interaction studies, since it becomes difficult to distinguish between the metal complex true action from its decomposition products’. Gold nanoparticles (AuNPs) are suitable drug delivery systems due to their good biocompatibility and ability to be conjugated with biomolecules. Therefore, a nanoconjugate of this kind (AuNP@PEG@BSA@CORM-3), featuring polyethylene glycol (PEG), BSA and CORM-3, was developed by the same group were the present work is included, showing better anti-inflammatory efficiency in human monocytes than CORM-3 by itself. Given the fact that one nanoconjugate can load hundreds of metal complexes, cellular uptake could be the reason behind their different efficiencies. Herein, such hypothesis is studied using Inductively Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES) as a way to quantify Ru and Au within cells. Although the collected data show possible sample preparation problems in the cell matrixes, the overall results point towards a much lower nanoconjugate uptake when compared to the free form of CORM-3, which seems incompatible with the suggestion previously made. Finally, the possibility of such nanoconjugate to be used therapeutically against Rheumatoid Arthritis, a chronic inflammatory disease, is explored using BSA as a carrier, as a preliminary assay for the nanoformulation, in Adjuvant-Induced Arthritic (AIA) rats. The lack of effect at a 0.0037 mg Kg-1 of CORM-3’s dose, rejects beforehand the possibility of this kind of system to be used against systemic inflammations.